Digital transformation of career landscapes in radiology: personal and professional implications - Agrawal, Anjali (Frontiers in Radiology, 2023)
Millennial radiology is marked by technical disruptions. Advances in internet, digital communications and computing technology, paved way for digitalized workflow orchestration of busy radiology departments. The COVID pandemic brought teleradiology to the forefront, highlighting its importance in maintaining continuity of radiological services, making it an integral component of the radiology practice. Increasing computing power and integrated multimodal data are driving incorporation of artificial intelligence at various stages of the radiology image and reporting cycle. These have and will continue to transform the career landscape in radiology, with more options for radiologists with varied interests and career goals. The ability to work from anywhere and anytime needs to be balanced with other aspects of life. Robust communication, internal and external collaboration, self-discipline, and self-motivation are key to achieving the desired balance while practicing radiology the unconventional way.